The Securing a Claim in the Context of Sustainable Development: An Evaluation of the Latvian Experience - Gvozdevičs, Andrejs (European Journal of Sustainable Development, 2021)
Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms provides for the right of everyone to a fair and public hearing by an independent and impartial tribunal established by law. An important guarantee, such as the enforcement of a court judgment, is also enshrined in human rights theory and practice, as unenforced judgments pose a threat to legal stability, which is one of the fundamental basis for the sustainable development of society. The institute of law of the securing a claim serves in cases where execution of the future judgment may be impossible or made substantially more difficult. The aim of the research is to study the legal framework, which determines the regulations of the securing a claim in Latvia in order to make proposals for enhancement of the legal framework. The research deployed descriptive, analytical and deductive-inductive methods as well as the methods of interpretation of legal norms. Using these methods, legal acts, views of legal scientists and case law were reviewed and analyzed, and subsequently conclusions and recommendations were made. Analyzing the development of the securing a claim it can be admitted that this institute of law in Latvia has problems as the application of the securing a claim in court practice within the framework of limited adversarial and dispositivity principles, as well as shortcomings in the theoretical foundations of the securing a claim which are based on the findings of legal scientists of the last century. As a result of the research, the author drew the conclusions, that Latvia does not make sufficient use of the long-standing successful procedural solutions for securing a claim in others states, such as court mortgages, bank guarantee or mortgage of the plaintiff to secure the defendant's losses, defendant's protection letter to protect against unjustified securing a claim, a possibility to secure a claims which are not financial in nature and many more that can make legal regulation of the securing a claim more modern and effective.